Psychosocial and Biochemical Impact of COVID-19 Pandemic on Mental Health of Medical Students - Ghazala Yasmeen Iqbal, Saba Sharif, Sadia Nikhet, Farrukh Adeel, Tariq Hussain, Naila Jabeen (Pakistan Journal of Medical & Health Sciences, 2023)
Background: COVID-19 (Coronavirus Disease 2019) is a highly contagious illness that originated in Wuhan, China, in December 2019 and rapidly spread to over 200 countries. The pandemic has impacted both physical and mental health globally. Among those affected, medical students have experienced significant psychological challenges, including anxiety, fear, and depression, along with disruptions to their academic progress. Objective: This study aims to evaluate the psychosocial and biochemical impact of the COVID-19 pandemic on the mental health of medical students at Sheikh Zayed Medical College, Rahim Yar Khan. Methods: An analytical cross-sectional study was conducted involving medical students from all five academic years at Sheikh Zayed Medical College during the period from July 2022 to December 2022. A total of 208 students (109 females and 99 males) participated by completing an online questionnaire assessing demographic data and psychosocial parameters, including depression levels using the PHQ-9 scale. Data analysis was performed using SPSS version 21, and results were presented in tabular and graphical formats. Results: Among the 208 respondents, most were boarders (76.4%) and under the age of 21. Depression symptoms varied across gender and residential status. Among day scholars, 91.84% reported no depressive symptoms, while among boarders, 86.79% had no signs of depression. Mild to severe depression was slightly more prevalent among females compared to males. Overall, the majority of students did not exhibit significant depressive symptoms. Conclusion: While a minority of medical students reported symptoms of depression during the COVID-19 pandemic, the overall mental health impact was notable. Academic performance and emotional well-being were affected, underscoring the importance of institutional mental health support during such crises. Keywords: COVID-19 Pandemic, Mental Health, Medical Students, psychological challenges, depression